ANALISIS KEMAMPUAN KOGNITIF MATEMATIKA MATERI OPERASI HITUNG PECAHAN MENGGUNAKAN VIDEO PEMBELAJARAN MATEMATIKA SISTEM DARING DI KELAS V SEKOLAH DASAR - Yantoro Yantoro; Suci Hayati; Latifatul Ulya (Universitas Negeri Medan, 2021)
This study aims to determine the cognitive ability of mathematics in the fraction count operation material using the online mathematics learning video system in class V of Elementary School No. 34 / I Lotus. The test was conducted to determine the students' cognitive abilities. There were 14 students out of 28 students who collected the test results. Based on the data analysis, it was found that the cognitive abilities of students in the high category were 6 students, while in the low category were 8 students. The results of the students 'high cognitive mathematics abilities were 50% and the students' low cognitive abilities were 50%. The results of observations from this study concluded that the students' lack of activeness during online learning using video lessons. This can be seen from the number of students who collected test results as many as 14 students out of 28 students. It can be concluded that students' cognitive mathematical abilities during online learning have different abilities. This can be seen from the level of student ability from the results of the tests carried out.Keyword: Cognitive Ability, Mathematics, Count Fraction Operations